Reactive granulomatous dermatitis as a clinically relevant and unifying term: a retrospective review of clinical features, associated systemic diseases, histopathology and treatment for a series of 65 patients at Mayo Clinic. (26th May 2022) - Bangalore Kumar, A.; Lehman, J.S.; Johnson, E.F.; Cantwell, H.M.; Sartori Valinotti, J.C.; Sokumbi, O.; Davis, M.D.P.; Wetter, D.A.
Abstract: Background: Reactive granulomatous dermatitis (RGD) is an umbrella term used to describe interstitial granulomatous dermatitis (IGD), palisaded neutrophilic and granulomatous dermatitis (PNGD), and interstitial granulomatous drug eruption (IGDR). Objective: The aim of this study was to describe systemic associations of RGD, explore possible associations between histopathologic findings and systemic RGD associations and determine clinical relevance of RGD subtypes. Methods: We retrospectively studied clinical and histopathologic characteristics of patients with RGD from 1990 through 2020. Results: Of 65 patients with RGD (41 women, 24 men; median age at diagnosis, 62 years), 37 had IGD, 26 had PNGD, and 2 had IGDR. Fifty patients (76.9%) had an associated systemic condition; rheumatologic conditions were identified for 34 (52.3%) patients. The associated systemic condition occurred before RGD in approximately 75% of patients. Statistical analyses did not show significant associations between specific subtypes of RGD and systemic diseases or treatment response, and specific histopathologic findings were not predictive of an associated systemic disease. Conclusions: Although most patients with RGD had an associated systemic condition, subtypes of RGD did not correlate with systemic associations, lending support to the use of the umbrella term RGD .